2009
DOI: 10.1111/j.1471-6712.2009.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Moods and expectancies of female alcohol drinking - an exploratory study

Abstract: Gaining access to information concerning mood states and expectations of change preceding a typical drinking occasion is important for understanding the trigger factors for drinking, and for alcohol abuse treatment planning. The objective of the present study was twofold: (i) to explore self-reported states of mood and expectancies preceding a typical drinking occasion vs. relations with parents and drinking outcome; and (ii) to investigate if vulnerability factors in terms of personality and health are relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…In an explorative Swedish study, Birath et al. (38) identified a new group of women with alcohol problems: fairly well‐educated, younger women of child‐bearing age and suggested alternative treatment. Even though the CAGE questionnaire is considered a valid tool, there may be undetected gender issues in using it that are often referred to as ‘natural’ gender differences based on the assumption that more men than women have problematic alcohol habits.…”
Section: Discussionmentioning
confidence: 99%
“…In an explorative Swedish study, Birath et al. (38) identified a new group of women with alcohol problems: fairly well‐educated, younger women of child‐bearing age and suggested alternative treatment. Even though the CAGE questionnaire is considered a valid tool, there may be undetected gender issues in using it that are often referred to as ‘natural’ gender differences based on the assumption that more men than women have problematic alcohol habits.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting work which was carried out on Swedish women suggested that the mood may be a factor which controlled the alcohol intake. The expectancy of reducing, fleeing or enhancing the mood which resulted from alcohol intake could be a motivator for alcoholism [13,14]. Social anxiety also produced a positive expectancy of tension reduction and increased the assertiveness in both men and women [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, earlier studies in women with dependence problems have shown that other factors in life seem to be of great importance for the women to process during the treatment period [26,27]. To prevent or mitigate psychiatric problems are important factors for the women still having custody over their children [37].…”
Section: Wwhmentioning
confidence: 99%
“…Most of them, like Motivational Interviewing (MI) [23], relapse prevention, and skills training [24,25] have a strong focus on the substance abuse problems only. The need to include additional aspects has been outlined in studies, for example the importance for women in treatment for their alcohol problems to discuss gender aspects, violence, and their children's situation [26,27].…”
mentioning
confidence: 99%